A comparison of Helicobacter pylori and non‐Helicobacter pylori Helicobacter spp. Binding to Canine Gastric Mucosa with Defined Gastric Glycophenotype. Issue 4 (2nd April 2014) - Amorim, Irina; Freitas, Daniela P.; Magalhães, Ana; Faria, Fátima; Lopes, Célia; Faustino, Augusto M.; Smet, Annemieke; Haesebrouck, Freddy; Reis, Celso A.; Gärtner, Fátima
Abstract Background The gastric mucosa of dogs is often colonized by non‐Helicobacter pylori helicobacters (NHPH), while H. pylori is the predominant gastric Helicobacter species in humans. The colonization of the human gastric mucosa by H. pylori is highly dependent on the recognition of host glycan receptors. Our goal was to define the canine gastric mucosa glycophenotype and to evaluate the capacity of different gastric Helicobacter species to adhere to the canine gastric mucosa. Materials and Methods The glycosylation profile in body and antral compartments of the canine gastric mucosa, with focus on the expression of histo‐blood group antigens was evaluated. The in vitro binding capacity of FITC‐labeled H. pylori and NHPH to the canine gastric mucosa was assessed in cases representative of the canine glycosylation pattern. Results The canine gastric mucosa lacks expression of type 1 Lewis antigens and presents a broad expression of type 2 structures and A antigen, both in the surface and glandular epithelium. Regarding the canine antral mucosa, H. heilmannii s.s. presented the highest adhesion score whereas in the body region the SabA‐positive H. pylori strain was the strain that adhered more. Conclusions The canine gastric mucosa showed a glycosylation profile different from the human gastric mucosa suggesting that alternative glycan receptors may be involved in Helicobacter spp. binding. Helicobacter pylori and NHPH strains differ in their ability to adhere to canine gastric mucosa. Among the NHPH, H. heilmannii s.s. presented the highest adhesion capacity in agreement with its reported colonization of the canine stomach.